APPLICATION OF MATHEMATICS TO OTHER FIELDS - Sulaymonov Ilyoskhuja (Лучшие интеллектуальные исследования, 2024)
Abstract. This article explores the pervasive influence of mathematics across various fields, highlighting its essential role in shaping our understanding and solving complex problems. From engineering to finance and computer science, mathematics provides the foundation for modeling, analysis, and optimization. Through examples ranging from structural engineering to option pricing and machine learning, this abstract showcases mathematics as a unifying language that transcends disciplinary boundaries, driving innovation and progress in diverse domains.